The Impact of Aligning Learning Processes with Technological Developments - The Emergence of The Concept of Education 4.0 - Ionuț-Claudiu POPA; Raluca-Giorgiana (POPA) CHIVU; Bianca Cristiana VOICU (Communications of International Proceedings, 2022)
Over 50% of the current workforce will need retraining by 2025. However, the ability to adapt to change and engage in lifelong learning must be developed early. Studies show that early investment in children's learning and Education generates significant economic benefits. As a result, tackling the core causes of the global skills gap would require investing in the development of holistic skills in primary and secondary school.. It is necessary to prepare the next generation of talent to engage in lifelong learning and ensure that future retraining and development efforts pay off. This will not apply to individuals, businesses and governments. In this article, we have conducted quantitative research in the form of a questionnaire, and among the objectives can be listed: analyzing the opinions of some students in Romania on how the education system evolves, highlighting the best tools that are used in learning processes and highlighting the state of the national education system. In terms of the results obtained, it can be highlighted that the Romanian education system is in a comprehensive process of development, that in our country, it is necessary to use policies that have proven to be successful and that have been used in other countries. , and internet of things technology can be one of the tools that can be used successfully to meet the standards of education 4.0.
Keywords: education 4.0; current events; educational future; evolution.